Assessment of microbial risk factors and impact of meteorological conditions during production of baby spinach in the Southeast of Spain. (August 2015) - Castro-Ibáñez, I.; Gil, M.I.; Tudela, J.A.; Ivanek, R.; Allende, A.
Abstract: There is a timely need to evaluate the effect agricultural factors and meteorological conditions on fresh produce contamination. This study evaluated those risk factors and described, for the first time, the distribution of indicator microorganisms ( Escherichia coli, Enterococcus, coliforms, and Enterobacteriaceae ) and the prevalence of foodborne pathogens (Enterohaemorrhagic E. coli, Listeria monocytogenes and Salmonella spp.) in baby spinach grown in the Southeast of Spain. A longitudinal study was conducted on three farms (2011–2013). Results obtained for E. coli highlighted soil and irrigation water as important factors affecting the microbial safety of baby spinach. Significant differences in the proportion of E. coli positive samples were found between treated (46.1%) and untreated (100%) irrigation water. However, the microbial quality of irrigation water didn't affect E. coli prevalence in produce. All E. coli positive spinach samples were detected at the highest observed temperature range suggesting that ambient temperature affects the probability and extent of spinach contamination. Salmonella spp. was detected by RT-PCR in manure, soil, irrigation water and baby spinach but only two of them (manure and irrigation water) were confirmed by isolation in culture media. Salmonella RT-PCR positive samples showed higher levels of E. coli than Salmonella negative samples. This preliminary finding supports recent identification of E. coli as a suitable parameter for the hygiene criterion at the primary production of leafy greens. Highlights: Soil and irrigation water were important factors affecting the microbial safety of baby spinach. Water treatments reduced the proportion of Escherichia coli positive samples of irrigation water. Water treatments represent a good intervention strategy to maintain a constant water quality. Ambient temperature affected the probability and extent of spinach contamination. E . coli was identified as a suitable parameter for the hygiene criterion at baby spinach production.